Inovasi Organisasi Bisnis: â€Belajar dari Inovasi Harian Jogja Ditengah Gempuran Teknologiâ€ - sunardi sunardi; fika fibriyanita (P3M Politeknik Negeri Tanah Laut, 2019)
This paper questioned the innovations by Harian Jogja in order to survive in the onslaught of technology advances. The research method in this paper is qualitative, and the result shows that Harian Jogja makes three innovations. First, innovation in the cover design, second,innovation in the content, and the third, they makes an innovation by created the anti malaria newspaper. The success of innovation in Harian Jogja influenced by cultural factors of organization, technical and learning organization.